The rolling dung master: An ecosystem engineer beetle mobilizing soil nutrients to enhance plant growth across a grassland management intensity gradient in drylands. (February 2022) - Barragán, Felipe; Douterlungne, David; Ramírez-Hernández, Alfredo; Gelviz-Gelvez, Sandra Milena; Guzmán Miranda, Andrea Valeria; Rodas Ortíz, Juan Pablo
Abstract: Dryland cattle pastures often yield sub-optimal economic returns while it intervenes with natural ecosystems functioning. Dung beetles improve soil conditions but little is known about how their functioning changes with different land management intensities. We assessed the role of the telecoprid dung beetle Canthon humectus in soil nutrient mobilization and commercial crop growth in arid grasslands with contrasting cattle managements. We set up a mesocosm experiment where we monitored dung beetle activity in containers filled with dung and soil from sites with three different cattle managements. Dung removal rates due to beetle burial activity were 10% higher than due to dehydration alone but was not affected by cattle management. After 60 days of beetle activity nitrates and ammonium levels increased significantly as compared with control pots without beetles. Additionally, we monitored corn plant growth in pots with soil with and without beetle activity. Plants significantly increased their biomass due to beetle activity in the substrate with the highest and lowest pasture management intensity. In the latter case, more biomass was allocated to shoots. The ability of C. humectus to increase soil nutrients and enhance plant growth is affected by local cattle management. Graphical abstract: Image 1 Highlights: Telecoprid dung beetle activity increases soil nitrogen and ammonium. Plant growth is accelerated in soils with dung beetle activity. Dung beetle function of C. humectus changes with grassland management intensity.